Stagnant Physical Therapy Referral Rates Alongside Rising Opioid Prescription Rates in Patients With Low Back Pain in the United States 1997–2010. Issue 9 (1st May 2017) - Zheng, Patricia; Kao, Ming-Chih; Karayannis, Nicholas V.; Smuck, Matthew
Abstract : Study Design: A cross-sectional observational study utilizing the National Ambulatory and National Hospital Ambulatory Medical Care Surveys between 1997 and 2010. Objective: The aim of this study was to characterize national physical therapy (PT) referral trends during primary care provider (PCP) visits in the United States. Summary of Background Data: Despite guidelines recommending PT for the initial management of low back pain (LBP), national PT referral rates remain low. Methods: Race, ethnicity, age, payer type, and PT referral rates were collected for patients aged 16 to 90 years who were visiting their PCPs. Associations among demographic variables and PT referral were determined using logistic regression. Results: Between 1997 and 2010, we estimated 170 million visits for LBP leading to 17.1 million PT referrals. Average proportion of PCP visits associated with PT referrals remained stable at about 10.1% [odds ratio (OR) 1.00, 95% confidence interval (95% CI) 0.96–1.04)], despite our prior finding of increasing number of visits associated with opioid prescriptions in the same timeframe. Lower PT referral rates were observed among visits by patients who were insured by Medicaid (OR 0.48, 95% CI 0.33–0.69) and Medicare (OR 0.50, 95% CI 0.35–0.72). Furthermore, visits not associated with PT referrals were more likely to be associated with opioid prescriptions (OR 1.69, 95% CI 1.22–2.35). Conclusion: Although therapies delivered by PTs are promoted as a first-line treatment for LBP, PT referral rates remain low. There also exist disparately lower referral rates in populations with more restrictive health plans and simultaneous opioid prescription. Our findings provide a broad overview to PT prescription trend and isolate concerning associations requiring further explorations. Level of Evidence: 3